Efficacy of acupuncture for persistent and intractable hiccups: A protocol for systematic review and meta-analysis of randomized controlled trials. Issue 8 (26th February 2021) - Zhang, Yu; Jiang, Xudong; Wang, Zhijie; He, Mingming; Lv, Zimeng; Yuan, Qing; Qin, Weixun
Abstract: Background: Persistent and intractable hiccups are a common clinical symptom that cause considerable physical pain to patients and severely damage their quality of lives. An increasing number of studies have demonstrated that acupuncture applied at acupoints dominated by Cuanzhu (BL2) can be used as one of the nonpharmacological therapies for controlling intractable hiccups. However, there is insufficient evidence evaluating the safety and effectiveness of those interventions. Therefore, this study is intended to conduct a systematic review and meta-analysis to provide evidence for a further study investigating alternative treatment options for persistent and intractable hiccups. Methods and Analysis: Randomized controlled trials (RCTs) of adult patients aged >18 years who meet the criteria for intractable hiccup diagnosis will be included, regardless of gender, nationality, and education level. Eight electronic databases will be searched, including 4 Chinese databases (CNKI, SinoMed, Wanfang Database, and Chinese Scientific Journal Database), 4 English databases (Web of Science, Medline, Embase, and Cochrane Library), from their date of establishment to September 2020. Two independent reviewers will evaluate the title summary for each RCT. Disagreements will be discussed with a third commentator. Data integration, heterogeneity analysis, subgroup analysis, and sensitivity analysis, will be performed using R-3.3.2 software. The RevMan 5.3 software will be used for the meta-analysis, and the "risk of bias" assessment will be conducted based on the methodological quality of the included trials recommended by the Cochrane Handbook 5.1. The quality evaluation of this study will be completed by the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE). Results: This study will summarize all the selected trials aimed at estimating the effectiveness, as well as safety, of applying acupuncture at acupoints dominated by Cuanzhu (BL2) to persistent and intractable hiccups. Conclusions: This systematic review will provide evidence to assess the validity and safety of applying acupuncture at acupoints dominated by Cuanzhu (BL2) for persistent and intractable hiccups, which may provide clinicians with more choices in the treatment of this disease. PROSPERO registration number: CRD42020114900.